The Impact of Financial Leverage on the Cost of Equity - Aharon, David Yechiam; Yagil, Yossi (International Journal of Economics and Financial Issues, 2019)
Using a sample of industrial companies traded on the NYSE, this study examines the effect of financial leverage (L) on the cost of equity (Ke). The goal is to test the theoretical relationship between Ke and L under various types of market imperfections such as taxes and bankruptcy costs, and compare theoretical models incorporating each market imperfection with actual values. All of the empirical results in each model tested point to a positive relationship between Ke and L regardless of the measures used for the key variables. Specifically, we establish four main findings: 1) The relationship between Ke and L is positive, 2) R-Squared is substantially higher in the risky debt models than in the risk free debt models, 3) The market measures of L tend to generate a higher R-Squared than the book measures of L, and 4) The model that is the most accurate representation of the relationship between the Ke and L incorporates a measure of risky debt. Thus, the findings suggest that risky debt should be employed in the estimation of Ke, otherwise Ke and the resulting weighted average cost of capital may be biased, leading to incorrect capital budgeting decisions. Keywords: cost of equity, financial leverage, market imperfections, risky debt JEL Classifications: G32, G33 DOI: https://doi.org/10.32479/ijefi.7554